Modeling of Economic Convergence Processes in Eastern Europe Countries - Stavytskyy , Andriy V.; Kozub , Maryna B. (Ekonomika, 2020)
The article describes the features of the processes of economic convergence in the countries of Eastern Europe for the last 10 years. The analysis of β- and σ-convergence was carried out based on a system of macroeconomic indicators with 10 key parameters. The calculation of the direction and speed of convergence was performed using the econometric instruments in the region as a whole and pairwise analysis of the β-convergence index for all analyzed countries. The obtained results allowed to conclude the inequity development of Eastern European countries and the lack of a stable trend towards convergence of macroeconomic indicators. The resulting model is universal and can be applied to other world regions or to determine the processes of convergence of another system of macroeconomic indicators and choose main directions of reforming to bring national economies closer and achieve stronger external relations.